Research on management and application of tunnel engineering based on BIM technology - Song, ZhanPing; Shi, GuiLin; Wang, JunBao; Wei, HaiMin; Wang, Tao; Zhou, GuanNan (Journal of Civil Engineering and Management, 2019)
The emergence of BIM technology has provided powerful technical means for realizing informatization and digitization in the field of engineering construction, which remarkably promotes the transformation and advance of production and management modes in engineering construction. Presently, the application and development of BIM technology in the field of engineering construction has become increasingly mature, yet in the field of tunnel engineering, the application of BIM technology is still in its infancy. Under such a circumstance, this paper first puts forward the basic hardware and software configuration requirements for BIM technology in tunnel engineering, and elaborates the basic structure of the BIM technology implementation team from eight respects. Second, this paper elaborates the general principles and the basic process of BIM technology application in tunnel engineering. Third, the paper proposes the initial construction scheme of the tunnel engineering collaborative management platform based on BIM technology, and analyzes the feasibility of platform development deeply. Last, the BIM technology is applied to two projects including Tunnel 1 in Yinxi Railway Huanxian County and Tianjin Metro Line 6, which provides auxiliary technical means for solving practical engineering problems, and provides some reference for subsequent application researches of BIM-like technologies in tunnel engineering.